Experimental study of CO2 adsorption in porous materials - Edry Rifdi Ahmad Nasir (Nanyang Technological University, 2021)
The major needs for mankind whether they are for daily living or industrial activity are the production of electricity, heating, cooling, and desalting water. Throughout the many years, these needs are primarily conventionally supplied by the burning of fossil fuels to generate electricity. However, burning of fossil fuels emits carbon dioxide (CO2) into the atmosphere, resulting in the CO2 concentration level being increased and contributing significantly to global warming. Therefore, carbon capture and storage (CCS) technology has been drawing attention as one of the most promising mitigation options due to its ability to capture CO2 from an industrial power plant and storing them by various means. One of the storage methods is adsorption technology, in which porous materials play an important role to store CO2 under various pressure and temperature. CO2 storage by the application of porous adsorbents is an economical method considering the low cost of equipment for operation and the possible recycling applications of the captured CO2. Various porous adsorbent such as activated carbon, silica gel, zeolite and metal organic frameworks (MOFs) have been extensively studied as adsorbents for CO2 capture and storage. However, MOFs proves to have one of the highest potential for CCS application due to its adjustable structure and properties. The overall aim of this research proposal is to develop a robust MOF-supported catalyst system for CO2 adsorption analysis, and the specific objective and scope are summarised as: • Fundamental understanding of porous MIL-101 (Cr) MOF and its modified versions namely 1-Butyl-3-Methylimidazolium-MIL-101 (1:1), 1-Butyl-3-Methylimidazolium-MIL-101 (1:2), 1-Ethyl-3-Methylimidazolium-MIL-101 (3:1), 1-Ethyl-3-Methylimidazolium-MIL-101 (2:1), 1-Ethyl-3-Methylimidazolium-MIL-101 (1:1) and 1-Ethyl-3-Methylimidazolium-MIL-101 (1:2) employing Ionic Liquid Implantation. • Experimental investigation for the measurement of CO2 uptakes on the assorted MIL-101 (Cr) MOFs under equilibrium and dynamic conditions. • Surface characteristics of these MOFs are calculated by SEM and TGA analysis. In this project, a volumetric set-up is utilized to measure the amount of CO2 for the pressure of up to 6 bar at ambient conditions, which meets the practical requirements of CO2 storage in a confined space such as solid-state adsorbents. The experimental results show that the implantation of ionic liquid (in terms of various mass ratio) on the parent MIL-101(Cr) MOFs improves the CO2 uptake.